The Implementation of MBKM Policy as a Government Communication Effort in Educational Transformation in Indonesia - Achmad Herman (STAI Hubbulwathan Duri, 2023)
The Freedom to Learn-Independent campus (hereafter, MBKM) policy provides opportunities for students to gain broader learning experiences and new competencies through some learning activities. Students are also free to take part in learning events that are not part of their study plan. It is important to follow this policy, so it needs to be shared with everyone who has an interest in it. This study aims to determine the extent of government communication in encouraging the successful implementation of the MBKM policy. This study used a quantitative approach, and the population was the MBKM unit (units or sections that facilitate students for MBKM activities) and students involved in the MBKM program, with a total of 100 respondents. Data were analyzed using descriptive statistics. Data were collected by distributing questionnaires. Data were then tabulated and processed using SPSS. The results showed that government communication in the implementation of the MBKM Policy was procedural (with a mean value of 4.97) and accountable based on government communication procedures (with a mean of 4,96). The implementation of MBKM policy was to provide benefits for students in terms of creativity and innovation as demonstrated by the implemented MBKM programs. Indeed, the implementation of this policy faced some weaknesses in that the government communication regarding MBKM is not fully on target and lacks efficacy (with a mean value of 3.00). It means that some policy implementers have not fully implemented the policies and some students are less interested in being involved in MBKM programs.